A superficial sulfur interfacial control strategy for the fabrication of a sulfur/carbon composite for potassium–sulfur batteries. Issue 12 (14th January 2021) - Hu, Lei; Meng, Xianghe; Liu, Lingli; Liang, Dewei; Liang, Sheng; Wang, Li-Li; Yang, Lei; Ding, Tao; Deng, Chonghai; Dong, Qiang
Abstract : Sulfur/carbon composite were successfully fabricated by interfacial control strategy, superficial sulfur was effectively removed by optimizing the ratio and amount of mixed solvents, thereby operating well in carbonate-based electrolytes. Abstract : Potassium–sulfur batteries in carbonate-based electrolytes cannot work well due to side reactions between polysulfide ions and ester molecules. Currently, removing superficial sulfur is an effective way to solve this issue. Here, we successfully achieved the deep encapsulation of sulfur and removal of superficial sulfur by a simple filtration-washing approach. As expected, the obtained products exhibited improved electrochemical stability and are promising candidates for better potassium–sulfur batteries.